Identification оf World Class Universities: Destructive Pluralism - E. V. Balatsky; N. A. Ekimova (Мир новой экономики, 2022)
The article deals with the problem of identifying world-class universities (WCU) on the basis of information provided by various ranking systems. The relevance of the problem is due to the fact that in 2022 Russia was “cut off” from the world community, including the interruption of cooperation with leading international ranking universities, so the country risks losing the opportunity to self-check its successes and failures by generally recognized criteria. In this regard, the purpose of this article is hypothesis verifcation that the “friendly” ranking of ARWU base can serve as an effective substitute for the “unfriendly” QS ranking base. To test the formulated hypothesis, we used the previously developed algorithm for identifying WCU using statistical data from the fve Global University Rankings — Quacquarelli Symonds (QS), Times Higher Education (THE), Academic Ranking of World Universities (ARWU), Center for World University Rankings (CWUR) and National Taiwan University Ranking (NTU) — and two University Rankings by subject — QS and ARWU. Conducted calculations disproved the general hypothesis and revealed a fundamental inconsistency of results obtained on the basis of different rankings. In addition, by the example of the ARWU, a profound contradiction in the logic of compiling the GUR and the SRU was uncovered. That raises a broader question about adequacy of the concept of the WCU itself. To answer this question, we conducted a “humanitarian test” for the validity of modern WCU, which showed the presence of elementary illiteracy and lack of culture among graduates of advanced universities. Collected stylized examples allowed to establish that modern world market leaders’ universities do not pass the “humanitarian test”, and therefore the entire rating system cannot be considered a reliable basis for conclusions about the activities of universities. The question of replacing the term WCU with a less pretentious “product” category — practice-oriented universities — is being discussed.